The "Getulian Works" through the Public Service Journal - Reis, Márcio Vinícius (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2015)
The Public Service Journal (JSP) - or the Civil Service Magazine , as it was also known - was the official print communication medium between the Estado Novo – or New State – government (1937-1945) and the civil service. It represented an important means of recording and propagandizing Getulian Works, or, in other words, the achievements of the Getúlio Vargas government, which in this case refers to federal public buildings. By assessing the period between 1937 and 1945, we have been able to reconstruct the mosaic of official architectural production over that period and understand the system created to coordinate it, which employed scientific principles of work rationalization applied to the public service. By means of the material gathered, especially documents on the works and exhibits, we have gained an understanding of the official architectural mindset, discourse and concerns in relation to erecting modern public buildings destined to house the various federal services and bodies.